The Effect of Nutritional Supplements and Rehabilitation Exercises on The Functional Adequacy of The Injured Deltoid Muscle in Bodybuilders - Abed, Nawres; Mahdi , Mustafa; Alhasan , Ahmed Muhammad (Journal of Physical Education, 2025)
This study aimed to identify the effect of nutritional supplements and rehabilitative exercises on the functional recovery of advanced bodybuilding players with anterior deltoid injuries. The experimental method was applied to two groups of eight injured athletes from the Baghdad/Al-Rusafa Gym. The first group performed rehabilitative exercises, while the second group combined them with nutritional supplements. Functional competence was assessed through measurements of muscle strength and range of motion using a dynamometer. The results showed significant improvement in both groups, with the combined program producing greater recovery. The study concluded that integrating nutritional supplements with rehabilitation exercises effectively restores the anterior deltoid muscle’s function and accelerates the return of injured bodybuilders to normal performance.